Covert preparation of a manual response in a ‘go’/‘no-go’ saccadic task is driven by execution of the eye movement and not by visual stimulus occurrence - Maioli, Claudio; Falciati, Luca (Frontiers in Human Neuroscience, 2015)
It has been recently demonstrated that visually guided saccades are linked to changes in muscle excitability in the relaxed upper limb, which are compatible with a covert motor plan encoding a hand movement toward the gaze target. In this study we investigated whether these excitability changes are time locked to the visual stimulus, as predicted by influential attention models, or are strictly dependent on saccade execution. Single-pulse transcranial magnetic stimulation was applied to the motor cortex at eight different time delays during a ’go’/’no-go’ task, which involved overt or covert orienting of attention. By analyzing the time course of excitability in three hand muscles, synchronized with the onset of either the attentional cue or the eye movement, we demonstrated that side- and muscle-specific excitability changes were strictly time locked to the saccadic response and were not correlated to the onset of the visual attentive stimulus. Furthermore, muscle excitability changes were absent following a covert shift of attention. We conclude that a sub-threshold manual motor plan is automatically activated by the saccade decision-making process, as part of a covert eye-hand coordination program. We found no evidence for a representation of spatial attention within the upper limb motor map.